Language Politeness in Discussion Activities of Class VIII Students - Warsoy, Abigael; Sasabone, Carolina; Tabelessy, Novita (Universitas Pattimura, 2023)
Politeness in language is a crucial factor in influencing pupils' linguistic development and character formation. Consequently, it is imperative to consider the dimension of politeness in pupils' linguistic expressions. This study seeks to delineate the deviations and adherence to the standards of linguistic politeness observed in class discussions among Class VIII students at SMP Negeri 7 Ambon. This study involved 33 kids from the eighth grade. The employed data collection methods included observation, interviews, recording, field notes, and documentation. The research findings indicate two categories of linguistic politeness: compliance with politeness rules and discourse, encompassing four debates with a total of 17 utterances, wherein all forms of maxims were identified. The second category encompasses transgressions from the standards of linguistic courtesy in discourse, categorized into three maxims and three utterances. The research findings indicate that the maxim most commonly violated is that of wisdom and appreciation, observed in breaches of the courtesy principle during discussions among Class VIII students at SMP Negeri 7 Ambon.